Zoledronate for Metastatic Bone Disease and Pain: A Meta‐Analysis of Randomized Clinical Trials. Issue 2 (28th December 2012) - Zhu, Min; Liang, Rui; Pan, Ling‐Hui; Huang, Bing; Qian, Wei; Zhong, Jian‐Hong; Zheng, Wei‐Wei; Li, Chang‐Long
Abstract Background Randomized controlled trials (RCTs) have reported different results when using zoledronate to treat skeletal‐related events (SREs) and bone pain in patients with metastatic bone disease (MBD), and few have looked at the risks and benefits of long‐term use of the drug. This meta‐analysis aimed to investigate the efficacy and safety of zoledronate to treat MBD in the short and long‐term. Methods PubMed, EMBASE, and the Cochrane Library were searched to identify RCTs evaluating zoledronate for MBD. Relative risks (RRs) and 95% confidence intervals (CIs) were calculated. Results Twelve RCTs involving 4, 450 patients were included in the meta‐analysis. Zoledronate decreased the risk of developing SREs compared with placebo (RR 0.75, 95% CI 0.69 to 0.81, P < 0.001). Zoledronate consistently reduced the brief pain inventory (BPI) below baseline compared with placebo at 3, 12, and 24 months. In addition, the likelihood of experiencing a bone pain event was significantly lower in the zoledronate group than in the placebo group (RR 0.83, 95% CI 0.76 to 0.89, P < 0.001). While the two groups did not differ significantly in the incidence of nausea(RR = 1.07, 95% CI 0.96 to 1.19, P = 0.250), emesis (RR 0.94, 95% CI 0.81 to 1.09, P = 0.420), or adverse renal events (RR 1.41, 95% CI 0.94 to 2.11, P = 0.09), the zoledronate group showed a significantly higher relative risk of pyrexia (RR 1.43, 95% CI 1.20 to 1.70, P < 0.001), fatigue (RR 1.26, 95% CI 1.10 to 1.43, P < 0.001), and anemia (RR 1.33, 95% CI 1.14 to 1.55, P < 0.001). Conclusion Compared to placebo, zoledronate significantly reduced the incidence of bone pain and SREs in patients with MBD for periods as long as 24 months. In addition, zoledronate is generally well tolerated over this long period.